2021
DOI: 10.3389/fmed.2021.719345
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is the Most Critical Risk Factor of Adverse Complications After Peritoneal Dialysis Catheter Placement

Abstract: Introduction: Peritoneal dialysis (PD) is a kind of renal replacement therapy for end-stage renal disease (ESRD). While PD has many advantages, various complications may arise.Methods: This retrospective study analyzed the complications of ESRD patients who received PD catheter implantation in a single medical center within 15 years.Results: This study collected 707 patients. In the first 14 days after PD implantation, 54 patients experienced bleeding complications, while 47 patients experienced wound infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…37 A retrospective, observational study of 707 patients in Taiwan showed that comorbid DM impacted on PD catheter-related infections (ESTIs and peritonitis) after catheter placement (OR 2.859). 38 The present study also showed almost the same outcomes as the Taiwan study.…”
Section: Discussionsupporting
confidence: 85%
“…37 A retrospective, observational study of 707 patients in Taiwan showed that comorbid DM impacted on PD catheter-related infections (ESTIs and peritonitis) after catheter placement (OR 2.859). 38 The present study also showed almost the same outcomes as the Taiwan study.…”
Section: Discussionsupporting
confidence: 85%
“…8 Risk factors for PD catheter exit-site infection, on the other hand, are better conceptualized by the relationship to the operation. Before catheter insertion, obesity, 49 poor diabetic control, 50,51 and S. aureus carriage status 52 are predictive of subsequent exit-site or tunnel infection. Once nasal S. aureus carriage is detected on screening, nasal antibiotic prophylaxis, such as mupirocin, should be used preoperatively.…”
Section: Environment-relatedmentioning
confidence: 99%